Phrasal Verbs in George Orwell’s 1984 and Its Arabic Translation (e-Journal of Linguistics, 2020)
n English, phrasal verb comprises of a verb and a particle, so does inArabic. Although both languages have phrasal verbs, it does not meanthat each phrasal verb in English is translated in the same form as aphrasal verb into Arabic. This research aimed to know the translationshift of phrasal verbs in George Orwell’s novel entitled 1984 and itsArabic translations. This research employed a qualitative descriptivemethod using a purposive sampling technique. The result showed thatArabic is a rich vocabulary language. It was proven by more than 50% ofthe English phrasal verbs found in the novel is translated into Arabic inthe same category or grammatical class, not in the form of description.
Keywords: Phrasal Verbs; Translation Shift; George Orwell’s 1984